UPAYA PENINGKATAN KOMPETENSI GURU DALAM PEMBUATAN SKENARIO PEMBELAJARAN INOVATIF MELALUI IHT (IN HOUSE TRAINING) DI SD NEGERI 1 WIROTAMAN - Bambang Dwi Subekti (INVENTA: Jurnal Pendidikan Guru Sekolah Dasar, 2019)
Considering the condition of teachers in Elementary School Wirotaman 1 Ampelgading Malang, which at the moment most of them still use the Learning Implementation Plan copy-paste results, and remember the importance of making innovative learning scenarios in a Learning Implementation Plan, on this occasion researchers intend to improve teacher competency especially in making innovative learning scenarios through In House Training in Elementary School Wirotaman 1 Ampelgading Malang" Based on the data obtained in the activity program implementation instrument in Cycle I which includes preparation, implementation, monitoring and evaluation activities, and reflection, it can be seen that the final score amounted to 80 with the Good category. In the implementation of Cycle II, the final number obtained was 84 with the Very Good category